Model Clinical Skill Self Efficacy (CSSE) Terhadap Kompetensi Klinis Mahasiswa Keperawatan - Didik Susetyanto Atmojo (Akademi Keperawatan Dharma Husada Kediri, 2016)
Introduction : Nursing student faced difficulties during clinical practice at the hospital, clinic and community. This research goal was to improved the nursing students competency using clinical skill self efficacy model. Methods: The study design of this research was exploratory survey with cross sectional approach, and quasy experiment. The samples were recruited from second years nursing students of Akper Dharma Husada Kediri that selected using simple random sampling technique, in total of 83 students. This research’s variables were beliefs, the clinical skill self efficacy and nursing student’s competency. The data were collected by using questionnaires and observation, data analyze by PLS and Wilcoxon sign rank test and Mann whitney. Results and Analysis: The result showed that individuals factors affected beliefs with path coeficient 0.387 and t- statistic value 4.769, psychological factors affected belief with path coeficient 0,492 and t- statistic value 5,984, beliefs factors influenced to thread with path coefficient 0,820 and t- statistic value 21,727 , thread influenced CSSE with path coefficient 0,506 and t-statistic value 5,927 , There were significant influenced on the implementation of a Clinical Skill Self Efficacy Model on nursing student clinical competency. Discuss and Conclusion: improved student competency using CSSE is carried out by building individual, psychologist, beliefs, thread factors.. The result on a dressing competency showed significant improved on communication, knowledge and psychomotor. Clinical skill self efficacy model can be applied on every clinical competency. Key words : Beliefs, CSSE, Clinical Competency